Emerging role of long non-coding RNA MALAT1 related signaling pathways in the pathogenesis of lung disease - Liu, Jun; Ali, Md Khadem; Mao, Yuqiang (Frontiers in Cell and Developmental Biology, 2023)
Long non-coding RNAs (lncRNAs) are endogenously expressed RNAs longer than 200nt that are not translated into proteins. In general, lncRNAs bind to mRNA, miRNA, DNA, and proteins and regulate gene expression at various cellular and molecular levels, including epigenetics, transcription, post-transcription, translation, and post-translation. LncRNAs play important roles in many biological processes, such as cell proliferation, apoptosis, cell metabolism, angiogenesis, migration, endothelial dysfunction, endothelial-mesenchymal transition, regulation of cell cycle, and cellular differentiation, and have become an important topic of study in genetic research in health and disease due to their close link with the development of various diseases. The exceptional stability, conservation, and abundance of lncRNAs in body fluids, have made them potential biomarkers for a wide range of diseases. LncRNA MALAT1 is one of the best-studied lncRNAs in the pathogenesis of various diseases, including cancers and cardiovascular diseases. A growing body of evidence suggests that aberrant expression of MALAT1 plays a key role in the pathogenesis of lung diseases, including asthma, chronic obstructive pulmonary diseases (COPD), Coronavirus Disease 2019 (COVID-19), acute respiratory distress syndrome (ARDS), lung cancers, and pulmonary hypertension through different mechanisms. Here we discuss the roles and molecular mechanisms of MALAT1 in the pathogenesis of these lung diseases.